Studi Sifat Fisika Tanah Pada Pertanian Hidroponik Potensi Dan Tantangan - Zebua, Siska Natalia; Waruwu, Inca Paskahlia (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Hydroponic farming, as a modern agricultural method, has shown great potential in increasing the efficiency of food production on limited land. Even though hydroponics does not directly use soil, understanding the physical properties of soil remains relevant in the context of developing efficient and sustainable growing media. This research aims to explore the physical properties of soil—such as texture, porosity, and density—and how these properties can be adapted to increase plant yields in hydroponic systems. In addition, this research identifies the challenges faced in implementing hydroponics, including limited knowledge about the interactions between growing media and plants, as well as economic and environmental aspects that need to be considered. Thus, it is hoped that this study will provide valuable insights for the development of more effective and sustainable hydroponic farming practices.